Elicitation of Systemic Acquired Resistance by a Novel Plant-Derived Biostimulant Composition Confers Robust Protection Against Botrytis cinerea in Tomato (Solanum lycopersicum L.) - Aleisha Wulandari; Sudarto Sudarto; Fifia Ardinanti; Bryan Helsey; Yi-Fen Huang (Natural Sciences Engineering and Technology Journal, 2025)
Gray mold, caused by the necrotrophic fungus Botrytis cinerea, is a devastating disease in tomato production worldwide, necessitating the development of sustainable and effective control strategies. Plant-derived biostimulants offer a promising eco-friendly alternative to synthetic fungicides by enhancing the plant's innate immune system. This study, conducted in greenhouse facilities in Palembang, Indonesia, evaluated the efficacy of a novel plant-derived biostimulant (PDB-MX7), a composition of Ascophyllum nodosum and Moringa oleifera extracts, in controlling gray mold in tomato (Solanum lycopersicum L. cv. 'Mutiara'). Tomato plants were treated with PDB-MX7 and subsequently inoculated with a virulent B. cinerea isolate. We assessed disease progression, plant growth parameters, and a suite of underlying defense mechanisms. These included the quantification of oxidative stress markers (H₂O₂, MDA), the activity of key defense-related enzymes (PAL, PPO, SOD, CAT), the accumulation of defense phytohormones (salicylic acid, jasmonic acid), and the expression levels of pathogenesis-related genes (PR-1, PDF1.2) via RT-qPCR. Pre-treatment with PDB-MX7 significantly reduced gray mold disease severity by 76.4% and lesion diameter by 71.8% compared to untreated, inoculated plants. This protective effect was associated with a significant priming of the plant's defense system. PDB-MX7-treated plants exhibited lower levels of H₂O₂ and MDA upon infection, indicating reduced oxidative stress. Furthermore, these plants showed a rapid and potent induction of PAL and PPO activity (3.1-fold and 2.8-fold higher than controls at 48 hpi, respectively). This was corroborated by a significant accumulation of salicylic acid and a more than 5-fold upregulation in the expression of the SA-responsive gene PR-1, indicating the activation of Systemic Acquired Resistance (SAR). In conclusion, the novel biostimulant composition PDB-MX7 confers substantial resistance against B. cinerea in tomato by priming the plant's innate immunity, primarily through the activation of the SA-mediated SAR pathway. This study highlights the potential of PDB-MX7 as a powerful tool for integrated pest management programs in sustainable tomato cultivation.